Vorticella sp: Prospective Mosquito Biocontrol agent - Chandrashekhar Devidas Patil; Chandrakant Prakash Narkhede; Rahul Khushal Suryawanshi; Satish Vitthal Patil (Tehran University of Medical Sciences, 2016)
Background: Considering the disadvantages of chemical insecticides, we aimed to evaluate Vorticella parasites for control of mosquito larvae of Anopheles stephensi and Aedes aegypti at different larval stages. Methods: Vorticella sp infected mosquito larvae were crushed in the 0.85% saline and homogenized well to get Vorticella in suspension. The effects of Vorticella sp infections on larval development were investigated by inoculating protozoan on different larval instars of An. stephensi and Ae. aegypti and observed under light microscope. Lethal time of the Vorticella infected larvae at different stages was calculated. Results: First and 2nd larval instars of both An. stephensi and Ae. aegypti did not show signs of infection by Vorticella sp., whereas 3rd instars of An. stephensi showed more Vorticella infection than those of Ae. aegypti. However, 4th larval instars of both mosquitoes were heavily infected with Vorticella parasite which was responsible for sluggish movements of larvae and eventually death. Moreover, parasites (Vorticella spp) were responsible for more than 90% reduction in adult emergence for both infected An. stephensi and Ae. aegypti. Conclusion: This study provides insights for mosquito larvicidal action of surface parasite Vorticella on different larval stages of An. stephensi and Ae. Aegypti. It could be suggested as a potential candidate in mosquito biocontrol programs.